Exploring the diversity of creative prototyping in a global online learning environment. Issue 2 (2nd April 2020) - Jablokow, K. W.; Zhu, X.; Matson, J. V.
ABSTRACT: In this paper, we examine the diversity of creative prototyping responses and perceptions in a global online learning environment through our investigation of a simple building task (i.e., 'the Shoe Tower') in the context of a Massive Open Online Course (MOOC) focused on creativity, innovation, and change. This simple creative task, which used common household objects (shoes), was designed and presented to a global community of online learners using the Coursera MOOC platform. Performance data gathered from the task outcomes (Shoe Tower metrics and number of build attempts) and student reflections (self-assessed beauty and creativity ratings) were analyzed with respect to gender, country of origin, and occupation. Our results show that gender and country of origin were associated with creative prototyping performance in statistically significant ways, while occupation was not. In addition, the self-assessment of individual creativity was independent of gender, country of origin, and occupation, while self-assessed beauty ratings were related to country of origin and occupation, but not gender.